Perilaku Toxic Dalam Game Mobile legend (Studi Pada Mahasiswa Pendidikan Sosiologi FKIP ULM) - Septiano Sihotang, Parlin Ariondo; Apriati, Yuli (Universitas Lambung Mangkurat, 2026)
Toxic behavior while playing Mobile legends is a common phenomenon among college students, including Sociology Education students. This behavior is evident through harsh language, insults, excessive emotion, and other negative responses that arise when players face stressful game situations. This study aimed to: (1) analyze the factors underlying Sociology Education students' toxic behavior while playing Mobile legends; and (2) identify the forms of toxic behavior that emerge during gameplay. This study employed a qualitative method with a case study approach. The informant selection technique used purposive sampling. The informants were five students who actively play Mobile legends and have engaged in toxic behavior. Data collection was conducted through observation, interviews, and documentation. Data were analyzed through the stages of data collection, data reduction, data presentation, conclusion drawing, and verification. Data validity was ensured through extended observation, increased diligence, and triangulation of sources, techniques, and time. The results of this study indicate that (1) the factors underlying toxic behavior among Mobile legend game players are: There are three, namely: a) Unable to control emotions, indicating that a player cannot control their emotions, when experiencing defeat and technical constraints (device and network). b) Social Environment (Peers): Social environmental conditions have an influence, making toxic communication more frequent within the scope of friendships in one hangout. c) Media Influence (YouTube Platform), toxic behavior is also influenced by media exposure, especially through platforms such as YouTube (2) Forms of toxic behavior that appear while students play the Mobile legend game. There are two forms, namely: a) Flaming in the form of insults, cursing and swearing (verbal) b) Expressive actions (Nonverbal).